Rattler one-seven : a Vietnam helicopter pilot's war story - Gross, Chuck, 1950- (North Texas military biography and memoir series, 2004)
"Rattler One-Seven" puts you in the helicopter seat, to see the war in Vietnam through the eyes of an inexperienced pilot as he transforms himself into a seasoned combat veteran